Trideset let zbirke serijskih publikacij v Občinski knjižnici Jesenice - Jamar, Nina (Knjižnica, 2020)
Purpose: The purpose of the article was to evaluate the collection of serial publications in the Jesenice Municipal Library and to set the goals for its future development. Methodology/approach: The methodology that we used is a comprehensive review of the collection of serial publications in the Jesenice Municipal Library for the last ten years and the comparison of these data to the to the Professional recommendations and standards for the public libraries: (for the period 2018-2028). Results: Most serials that are part of the collection of serial publications at Jesenice Municipal Library, are classified in UDC group 0. Using COBISS3 software and its segment Serial publications highly facilitated the management of the serials collection. The correspondence of the serial publication collection with the quantitative indicators for library collection listed in the General Recommendations and Standards for local public libraries from 2018 regarding the acquisition of serials is 58 %. According to the professional recommendation the acquisition of serials for readers up to the age of 15 should also be increased. The lending of serial publications and the number of visitors of reading room that is a part of Jesenice Municipal Library decreased for about 35 % in the last years. Research limitations: Since 2006 COBISS3 software and its segment Serial publications is used for managing the collection of serial publications. Before that the date important for the management of the collection were hard to acquire. Originality/practical implications: The results will serve as a basis for planning further work related to serials publications at the Jesenice Municipal Library.
Keywords: Jesenice Municipal Library; Občinska knjižnica Jesenice; public libraries; serial publications; serijske publikacije; splošne knjižnice